Factores causantes del impétigo en niños menores de 5 años, usuarios del Centro de Salud Arajuno, Provincia De Pastaza. Año 2013 - 2014 - López Rodríguez, Iliana Alexandra (2015)
The research had the purpose to define the factors causing impetigo. The impetigo is an infection, which affects the skin and face and is produced by two types of bacteria. This is a special subject that was chosen since the attendance rate of children, in the medical consultation is very high. The target of this research is to reduce or avoid the spread to other family members because the contagious of impetigo has serious consequences. The target of the research are 50 children under 5 years old in the Medical Center of Arajuno, Pastaza Province. The design of this research is primarily descriptive, cross-fixed and field. The survey and observation was used as techniques in gathering information with its tools, the questionnaire and the observation guide. One of the important result that got the research is that 88% of mothers are not informed and aware of preventive measures to avoid contagious from others. Verify that can be obtained in this research is to foster and promote to the mothers about the preventive methods to avoid infection and appearance of impetigo. Even more the research shows that people that was under the research lacks the basic services for a good livelihood by making it difficult to maintain a healthy lifestyle so according to the results obtained it is necessary to develop a proposal to combat the causes of the presence of impetigo Finally the result of this research is an educational manual and triptych. Atty. Personnel Coordinator as educational material support. Keywords: Impetigo, causative factors, children under 5 years